Understanding of Posyandu Cadres in Early Detection of Stunting: Pemahaman Kader Posyandu Didalam Mendeteksi Dini Stunting - Ardila Lau; Niluh Nita Silfia; Novi Dwi Astuti; Hasnawati; Narmin; Asriwidyayanti (Poltekkes Kemenkes Palu, 2024)
Background: SSGI data in 2021 shows that the prevalence of stunting cases in Indonesia amounted to 5.33 million stunted children under five (24.7%). Cadres play an important role in the implementation of posyandu as one of the activities to monitor the nutritional status of toddlers, where the results of the initial survey of cadre knowledge and skills are still lacking. The purpose of the study is to determine the relationship between the level of knowledge of posyandu cadres and the ability to detect stunting early in the Working Area of the Pantoloan Health Center, Palu City. Methods: Type of research with analytical survey method with Cross sectional approach. The research was conducted on May 6 - 18, 2024. The population is 85 posyandu cadres from 17 posyandu and the sample is 46 posyandu cadres according to the inclusion and exclusion criteria. The independent variable is the mother's knowledge. The bound variable is the ability to detect stunting early. Data collection uses questionnaires. Univariate and bivariate data analysis. Result: Chi Square test with a p value of 0.000 (< 0.05) then Ha is accepted. Conclusion: there is a relationship between the level of knowledge of posyandu cadres and the ability to detect stunting early in the Working Area of the Pantoloan Health Center in Palu City.